ANALISIS KALKULASI BODY MASS INDEX DENGAN PENGOLAHAN CITRA DIGITAL BERBASIS APLIKASI ANDROID - Hilman Fauzi; Nasya Ayudina Darsono; Bambang Hidayat . (Jurnal Elektro dan Telekomunikasi Terapan (e-Journal), 2018)
In 2000 WHO estimated that over 700 million adults will be overwight in 2015 and there’s an increase in the prevalence of obesity up to 50% by 2025 in developed countries. To reduce this risk, there is a standard formula which was lauched by World Health Organization called Body Mass Index (BMI). BMI is an index which referred a standard posture of normal and abnormal healthy human. This index is generated by formula that involves the calculation of proposed human posture approach. In this study, BMI can be calculated by image processing in android application. This proposed method use spatial techniques which digital image will be cropped to get RoI as width and height of a person. Then, the pixels will be processed with normalization to get height and width of RoI pixels calculation for BMI using an elliptical cylinder formula to get the Body Surface Area (BSA) and height pixel after normalization. As the results of the application system design, the BMI performance using digital image processing has an optimal accuracy in up to 91% from 480x640 of camera resolution.